Albuminuria-based stratification of end-stage kidney disease progression and mortality with sodium-glucose cotransporter 2 inhibitors (SGLT2i): A retrospective cohort study in type 2 diabetes and chronic kidney disease - Chang, Tien-Jyun; Lee, Yen-Chieh; Wu, Li-Chiu; Chang, Chia-Hsuin (Pharmacotherapy, 2024)
Clinical trials have shown the kidney-protective benefits of sodium-glucose cotransporter 2 inhibitors (SGLT2i). However, their real-world impact, particularly across varying levels of albuminuria, remains less well understood. This study aimed to evaluate the association of SGLT2i, compared with other oral glucose-lowering drugs, with end-stage kidney disease (ESKD) progression in patients with type 2 diabetes and chronic kidney disease (CKD) stratified by urine albumin-to-creatinine ratio (UACR) levels. Using data from a national database spanning from 2016 to 2021, the study included patients with type 2 diabetes and CKD with estimated glomerular filtration rates (eGFRs) below 60 mL/min/1.73 m and who started on SGLT2i or other oral glucose-lowering drugs. Patients were stratified into groups by UACR ≥300 mg/g and <300 mg/g. Propensity score matching was used to minimize confounding, and progression to ESKD was evaluated using competing risks and Cox proportional-hazards models. All-cause mortality was also analyzed. Following propensity score matching, 18,514 patients in the severely increased albuminuria group (UACR ≥300 mg/g) were tracked, with 2.6% progressing to ESKD over 3 years. In contrast, only 0.3% of the 26,946 patients with UACR <300 mg/g progressed to ESKD. SGLT2i use was associated with a 30% reduction in risk of ESKD progression, compared with the use of other oral glucose-lowering drugs, in the severely increased albuminuria group (hazard ratio[HR]: 0.70, 95% confidence interval [CI]: 0.61-0.80). In the lower albuminuria group, no significant association was evident, though there was a nonsignificant trend toward protection over time. A consistent reduction in mortality risk was observed across all albuminuria levels. SGLT2i are associated with a reduction in the progression to ESKD among patients with severely increased albuminuria, with less pronounced effects observed in those with lower albuminuria levels, suggesting variability in renal outcomes based on albuminuria severity. The consistent survival benefit across all albuminuria levels supports the potential utility of SGLT2i in diabetes and CKD treatment strategies, emphasizing the need for more targeted research.